2011
DOI: 10.1088/0960-1317/22/1/015002
|View full text |Cite
|
Sign up to set email alerts
|

Thin-film stretchable electronics technology based on meandering interconnections: fabrication and mechanical performance

Abstract: A new fabrication technology for stretchable electrical interconnections is presented. This technology can be used to connect various non-stretchable polyimide islands hosting conventional electronic components. The interconnections are realized by patterning a 200 nm thick sputter-deposited gold film into meandering horseshoe shapes, functioning as 'two-dimensional springs' when embedded in a silicone elastomer. Polyimide support is introduced around the meandering conductors as a means to improve the mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
88
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 19 publications
3
88
0
1
Order By: Relevance
“…They found that a "horseshoe" shaped track with a conductive width as small as possible was the best solution, and they reported elongation at break up to 100%, which is slightly above the non-optimized zigzags tracks of Perlrine et al presented in the previous paragraph. The technique was further developed by Verplancke et al by sandwiching the meandering track between two spin-coated polyimide layers as a means to improve mechanical performance [51]. They obtained reproducible uniaxial stretching up to 100% without noticeable change in resistance (R 0 ≈ 180Ω) or hysteresis.…”
Section: Patterned Metal Electrodesmentioning
confidence: 99%
“…They found that a "horseshoe" shaped track with a conductive width as small as possible was the best solution, and they reported elongation at break up to 100%, which is slightly above the non-optimized zigzags tracks of Perlrine et al presented in the previous paragraph. The technique was further developed by Verplancke et al by sandwiching the meandering track between two spin-coated polyimide layers as a means to improve mechanical performance [51]. They obtained reproducible uniaxial stretching up to 100% without noticeable change in resistance (R 0 ≈ 180Ω) or hysteresis.…”
Section: Patterned Metal Electrodesmentioning
confidence: 99%
“…The approach of metal meanders was mainly used to fabricate highly conductive stretchable interconnects 29 and antennas 53 . Later, the geometry and preparation of the meanders was further optimized to horseshoeshapes 20,30,144 or self-similar 32,52 designs embedded into microstructured polymer supports, which makes these interconnects able to accommodate up to some hundred percent of tensile deformation.…”
Section: Meanders and Compliant Patternsmentioning
confidence: 99%
“…To make these interconnections mechanically stretchable, 2 approaches have been adopted. In a first approach, traditional conductors such as copper, gold or silicon are patterned as spring-like structures instead of straight lines [4][5][6][7]. In a second approach, an electrically conductive stretchable material itself is used to create the interconnections [8].…”
Section: Introductionmentioning
confidence: 99%